Psychosis as the sole presenting feature of hyperthyroidism: a case report - Tuteja, Vinay; Nawal, C. L.; Singh, Aradhana; Chejara, R. S.; Singh, Rajbeer; Chouhan, Siddharth (International Journal of Research in Medical Sciences, 2018)
Thyroid disease is a very common entity with a wide range of presentation, We report a case of twenty six year old female presented to emergency room with frank psychosis over the course of her stay in hospital we investigated thoroughly and finally she turned out to be a case of hyperthyroidism with psychosis as the only presenting symptom and after starting her on carbimazole patient responded to the treatment remarkably.